(untitled) (Research, Society and Development, 2021)
This work presents some considerations regarding gastrointestinal disorders in a patient diagnosed with COVID-19, as well as the relationship between fecal-oral transmission. From then on, the intention of the study is to generate greater clarity on the research topic to the reading public. Thus, the objective is to analyze research articles and bibliographic reviews aimed at gastrointestinal disorders associated with infection by the SARS-VOC-2 virus. For the consolidation of its objective, it was necessary a study focused on the systematic review of the literature, which used 07 articles published in the year 2020 and 2021, complete and available for free downloads, in the Portuguese language. Incomplete articles from the literature review were excluded from the search, and outside the time set for the research. The study showed the relationship of gastric symptoms associated with patients with the SARS-COV-2 virus, as well as presented data on means of hygiene care to cope with the disease. After the analysis of the selected studies, it is concluded that the request for abdominal radiologies for the patient’s prognosis is of great scientific relevance.